Review of Clustering Algorithm for Cluster Head Selection of MANET Using Weighted Metrics - Monga, Sandeep; Rana, J.L; Agarwal, Jitendra (International Journal of Computer Sciences and Engineering, 2018)
A Mobile Ad hoc Network (MANET) is an accumulation of wireless portable nodes shaping a system without utilizing any current infrastructure. The mobility characteristic of MANETs is an extremely critical one. The mobile nodes may follow different mobility patterns that may affect connectivity and performance. In MANET due to decentralize of resources every nodes have to perform the routing functionalities themselves. Communication in such type of network is challenge and complex. To overcome these problems Clustering is the best solution for wide, flexible and high portability Ad-Hoc System. It increases the potential of network and reduces the routing overhead for efficient routing in MANET. Different types of phases involve in Cluster are Designing of Cluster and Maintenance of Cluster. In Cluster designing, selecting proper cluster head is one of the primary issues of research. For Maintenance of cluster an efficient system is required so that cluster head can keep update all the data of cluster, due to change in cluster structure because of nodes mobility. This paper basically focused on the Weighted Metric algorithms in MANET.